THE QURAN INSIGHTS ABOUT TEACHER PROFESSIONALISM (Thematic Interpretation APPROACH) - Wahyu Sakban; Asnil Aidah Ritonga (Universitas Dharmawangsa, 2022)
ABSTRACT Education is a theory born from human thinking about educational problems and efforts to solve them systematically and fundamentally. And education is also included in the practice applied in human activities to educate students in order to achieve certain expected goals. Professionalism itself is an understanding that teaches that every job or profession must be done by a professional person. In Islam, all work must be done in a professional manner, in the sense that it is done properly and correctly. This can only be done by an expert like that. whatever type of profession a person has, he should do it professionally. Therefore, this article is deliberately made to discuss the professionalism of teachers and what terms are used in the Qur'an in the world of education. There are various terms God conveys to humans related to the meaning of professionalism, for example in the letters Al-An'am: 135 and Al-Isra” 84 which has a meaning in the style of ala yang mana man Atiku and the word ala syakitraini which has the meaning of degree, place, the writer can draw the term understanding that the Qur'an gives a signal that a job must be done professionally. Likewise, the teaching profession must be carried out professionally in educating students.